Pelatihan TOEFL sebagai upaya meningkatkan kemampuan bahasa inggris dan pengembangan karier bagi Mahasiswa Fakultas Syariah UIN Salatiga - Saputra, Heru (Nur Science Institute, 2022)
English is something that must be mastered in this era of globalization. One indicator of English proficiency is the TOEFL score. The purpose of this training is to improve the ability of UIN Salatiga Sharia Faculty students in 2022 to work on TOEFL questions. The participants in this training were 30 Sharia faculty students from various semesters who had been selected through portfolios. This training method involves a pretest, hybrid lectures (online and offline), and a post-test. The result of this study is an increase in student TOEFL scores from a minimum initial score of 310 to 350. Furthermore, the average score in the pretest is 315 to 375 in the post-test.